马六甲英华书院的儒家论述 (A Study On The Confucian Discourse Of The Anglo-Chinese College At Malacca) - Chan, Pei Wen (2020)
The history of Southeast Asian Confucianism normally began with the Confucian Revival Movement in Malaya between nineteenth and twentieth centuries. The rediscovery the Confucian Discourse of the Anglo-Chinese College at Malacca will push back the initiation point toward the early of nineteenth centuries. By focusing on the internal difference of preaching strategy of the Anglo-Chinese College, this study discovers the China-oriented faction of the missionaries within, together with its development. The college was actually divided into two departments, the Chinese and the Malay which shared the missionary, scholar and publishing resources. But due to the bias of the founders from the internal and the influence of the scholarly, political and business fields from the external, the college eventually became a pro-Chinese London Missionary Society divisional institution at Malacca. The interpretation of and criticism on Confucianism of the college was originated from the China-oriented faction, which had a strong proposition to transcend Catholicism. Thus, the faction suggested a full prohibition of idolatry in order to prove itself a more orthodox denomination as compared to Catholicism which accepted the worshipping of the ancestors and Confucius. Besides, they also emphasized on the difference between the Chinese flood and Noah flood in order to oppose the figurism approach. However, the faction failed to transcend the “The Former and Latter” ABSTRACT iii philosophy historical framework of Catholicism. This study also analyses the faction from the colonial context, where the pioneers discriminated against the Malay society, perceiving the war and colonization as proper missionary tools, yet had a reciprocal even collaborative relationship with scholarly, political and business fields. Its confusion discourse was also greatly influenced by western superiority, criticizing Confucianism more aggressively than its ridicule on Catholicism, and opting for an ineffective critical approach in order to highlight their prominence over Confucianism.